Fan Identity Construction and Identity Expression in Cyberspace: A Study Based on Virtual Communities - Fanlu Pan; Hassan, Hanita (International Journal of Computational and Experimental Science and Engineering, 2025)
The identity construction and performance have shifted profoundly over the period of the digital virtual communities. In view of this, the objectives of this research are as follows: To understand how fans construct and perform their identity in cyberspace; using fan communities as exemplars. It can be said that while fan identity was long linked to dedicated fan sites and Buffy could have been an ideal example for that, the new forms of fan communities, that came with the attract of platforms like Reddit, Tumblr or Twitter – among others – turned the notion of fans into a dynamic, constantly evolving process. This research adopts a concurrent mixed-methods model to explore the processes of becoming a fan and to engage in fandom. First, the research employs non-probability purposive qualitative in-depth interview method to assess the fans and gain an understanding of their perceptions and the fan community experiences. Second, the study also uses quantitative online surveys to assess the fan communities, and provide a statistical representation of the whole fan community. Specifically, the research examines how people create virtual communities as a way of constructing fan identity in relationship to self-values, feelings, and affiliations; and as a way of play, using aliases allowed by cyberspace. The work of identity in the present study reveals that to become fans, viewers participate in conversations, produce fan materials and culture, or align themselves with the views and values of the community. The research also emphasizes the importance of social media platforms as the places where identity can be performative, and features like avatars, usernames or shared content create significant tools for personal and fan identity.